2001
DOI: 10.1292/jvms.63.625
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Pig Discrete Peyer's Patches: Expression of Surface Antigens.

Abstract: ABSTRACT. Leukocyte populations present in the discrete Peyer's patches (PP) of the pig were characterized from birth (Day 0) to day 35 after birth by immunohistochemistry and image analysis. Immediately after birth, cell membrane expression of CD2 and CD3, major histocompatibilty complex (MHC) class II (both SLA (swine leukocyte antigen) -DQ + and SLA-DR + ), CD21, 74-22-15 and surface immunoglobulin (sIg) were all demonstrable. Computer assisted morphometric techniques were used to confirm the significant ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Subsequent to immune induction, the lamina propria has proven to function as the regulator of immune responses in the intestine (Makala et al, 2001). The gastrointestinal lamina propria is composed of smooth muscle cells, fibroblasts, blood vessels, and lymphatics that make up a highly vascular layer of loose connective tissue underlying and supporting the mucosal epithelium (Hunyady et al, 2000).…”
Section: Galt Effector Sitesmentioning
confidence: 99%
“…Subsequent to immune induction, the lamina propria has proven to function as the regulator of immune responses in the intestine (Makala et al, 2001). The gastrointestinal lamina propria is composed of smooth muscle cells, fibroblasts, blood vessels, and lymphatics that make up a highly vascular layer of loose connective tissue underlying and supporting the mucosal epithelium (Hunyady et al, 2000).…”
Section: Galt Effector Sitesmentioning
confidence: 99%
“…Again, it was apparent that several subsets of APC were present, identified by different intensity of immunohistochemical labelling with the porcine myeloid marker SwC3, now known to be the porcine homologue to CD172a (SIRPα) [69]. In a second study, cells were also isolated from pig PP based on their low buoyant density [68].…”
Section: Peyer's Patchesmentioning
confidence: 99%
“…In parallel studies [22][23][24][25][26] have shown that Mø can differentiate into functional DC. Exposure to macrophage colony-stimulating factor (M-CSF) induces only macrophage formation, whereas granulocyte-macrophage colony-stimulating factor (GM-CSF) also induces DC formation [28,49].…”
mentioning
confidence: 97%
“…Peyer's Patches (PP) are the major organized lymphoid structures involved in the induction of mucosal immune responses in the intestine [22][23][24]. Joseph Conrad Peyer in 1677 provided the first accurate description of these discrete lymphoid aggregates in the intestinal wall, which have come to bear his name [14,35].…”
mentioning
confidence: 99%
See 1 more Smart Citation